88.5k views
4 votes
Use the numbers below to simplify the expression. Numbers may be used once or not at all. 34671011 3y + 7 + 4y + 3 = y +

1 Answer

6 votes

Answer:


3y + 7 + 4y + 3 = 7y + 10

Explanation:

Given


3y + 7 + 4y + 3 = [\ ]y + [\ ]

Required

Simplify

We have:


3y + 7 + 4y + 3

Collect like terms


3y + 7 + 4y + 3 = 3y + 4y + 7 + 3

Evaluate like terms


3y + 7 + 4y + 3 = 7y + 10

User Gerald Ferreira
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.